Calf Morbidity and Mortality: Critical Challenges for Smallholder Dairy Farmers in Northern Ethiopia - Gebreyohans Gebru; Gebregergs Tesfamaryam; Dawit Gebremichael; Gebremedhin Romha; Angesom Hadush; Tsriti Gebremeskel; Kiros Kelkay; Moges Gebremichael; Alem Beyene; Haftom Hadush (Veterinary Medicine International)
Calf morbidity and mortality pose significant economic challenges for smallholder dairy farms in Ethiopia, resulting in direct losses from calf deaths, replacement costs, treatment expenses, and reduced lifetime productivity. This study aimed to comprehensively investigate the magnitude and epidemiological characteristics of calf morbidity and mortality in Northern Ethiopia. A cross-sectional study with mixed approaches was carried out from December 2019 to September 2020. A total of 183 questionnaire survey, four focus group discussion (FGD), and 17 key informant interviews (KII) were included in the study. Furthermore, participatory epidemiological appraisals were incorporated to triangulate and strengthen survey evidences. Analysis of survey results revealed that 69.4% of the farmers have experienced calf morbidity, while 63.9% of them have encountered calf mortality. Similarly, results of proportional piling indicated that calf morbidity and mortality were estimated to occur in 75.5% and 55.9% of the farms, respectively. Moreover, all KIIs had encountered calf morbidity, while 88.2% of them had faced calf mortality. Ninety percent of KIIs, 66.2% of the participants of community-based epidemiology, and 27.87% of questionnaire survey respondents suggested that calf morbidity and mortality occur in less than one-week-aged calves. Regarding the potential risk factors, source of water, frequency of barn disinfection, breed types, health status of dams, using separate calf housing, amount of colostrum provided to calves, and cleaning frequency of barns had statistically significant association with the occurrence of calf morbidity and mortality (p<0.05). Additionally, results of participatory appraisal, FGDs and KIIs showed that calf diarrhea, nutritional disorder, pneumonia, and navel ill were the leading causes of calf morbidity and mortality. Furthermore, observation assessment showed that most dairy farms were surrounded by dense human settlements, livestock markets, and municipal slaughtering houses. Hence, the farms had critical space limitation (for animals to exercise) as well as poor drainage systems and hygienic practices. Our assessment also showed that lack of veterinary services, shortage of water supply, and poor artificial insemination services were the major challenges of dairying in the area. In conclusion, the present study revealed that calf morbidity and mortality were critical challenges for dairying in Northern Ethiopia. Furthermore, the study highlighted the epidemiological characteristics and potential risk factors associated with calf morbidity and mortality, awareness gaps in calf management, as well as key bottlenecks in dairy farming. These findings underscore the need for a comprehensive study, continuous capacity building initiatives, improved infrastructure, and services to mitigate calf losses.